Perspective positioner - ZHONG BAOMEI; SUN XIAODONG; SUN XIAONING; AI CHUNXIAO (2011)
The invention relates to a perspective positioner with a positioning function and a protective isolation function. The positioner is in a cover shape which is consistent with that of a receiver or a transmitter of an X-ray machine, comprises a positioning part, a cover surface, a cover edge and a cover edge bayonet, is made of a plastic material which X-rays can permeate, is positioned in the geometric center of the cover surface and is vertical to the cover surface. The positioner on the cover of the X-ray machine can acquire an accurate and satisfying image as long as the positioning part is aligned with an area which is needed to be irradiated to perform perspective shooting; and the positioner is sterile and can prevent an operation area from being polluted by the X-ray machine so as to greatly improve an accurate imaging rate and reduce the infection probability to the greatest extent.